Fracture performance of epoxy foam: Low density to bulk polymer. (18th November 2022) - Irven, George; Carolan, Declan; Fergusson, Alexander; Dear, John P.
Abstract: Epoxy foams with densities ranging from 180 to 500 kg/m 3 were prepared and mechanically tested in compression, tension, and single-edge notched bending (SENB) configurations. Fracture results revealed a marked transition in behaviour at a critical density, between 227 kg/m 3 and 249 kg/m 3 . Lower density foams failed at low SENB displacement, producing low toughness and fracture energy results, whereas higher density foams failed at higher SENB displacements, with correspondingly higher values of toughness and fracture energy. The stress-intensity factor increased monotonically with density, from 0.1 to 0.79 MPa m 1/2 . The fracture energy, G I c, of the foams reached values of up to 3.5 times that of the bulk polymer, 268 J/m 2 . Lower density foams below the transition in fracture behaviour exhibited a small number of large cells, caused by cell coalescence, and a wider cell size distribution than the denser foams. This distribution appears linked to the transition in fracture behaviour. The behaviour revealed in this paper raises the point whether in future design criteria, where foams are now often used in composite sandwich structures, allowance should be made for denser foams to be used as appreciable increases in fracture energy of the foam core are achievable. Graphical abstract: Image 1 Highlights: The fracture performance of epoxy foams varies as a function of density. Large increase in fracture energy occurs over a small increase in foamed density. A transition density from conventional foam fracture behaviour to a tougher behaviour can be identified. Designers should consider the improved fracture performance of slightly denser foams.